Acá debemos elaborar nuestra propia política - Hugo Blanco; Vicente Romero (Les Cahiers ALHIM)
In this interview the indigenous leader refers particularly to the development of the peasant movement from La Convención (Cusco) and the actions leading to the retake of the land, to make the peasant agricultural reform and for their self-defence. He describes also it’s own theoretical and political path, accomplished with his entire involvement in the indigenous people’s fights and the problems facing this people and the humanity.